Air conditioner - Chen Qifan; Gu Yuhui; Yang Tianyou; Jia Xiaoxing; Wan Jiong; Ma Junfeng; Li Qing; Wu Chaoliang (2016)
The invention discloses an air conditioner which comprises an electric control box and an air conditioner shell. Guide rails and pull-limiting units are arranged at the top of the air conditioner shell. The electric control box is connected with the guide rails in a sliding mode. The pull-limiting units are fixed to the side, close to the pulling direction of the electric control box, of the top of the air conditioner shell. Pull handles are further fixedly connected to the side, close to the pull direction, of the electric control box. The air conditioner is simple in structure, the electric control box and the air conditioner shell of the air conditioner are integrated, and the electric control box can be detected, repaired and upgraded simply and conveniently in a pulling mode. 本发明公开种空调器，包括电控盒和空调壳体，所述空调壳体顶部设置有导轨和抽拉限位，所述电控盒与所述导轨滑动连接，所述抽拉限位固定在空调壳体顶部靠近电控盒抽拉方向的侧，所述电控盒靠近抽拉方向的侧还固接有拉手。该空调器结构简单，实现了空调器的电控盒与空调壳体组合为体，通过抽拉方式简便地对电控盒进行检测、维修与升级。